2019
DOI: 10.1590/0100-29452019036
|View full text |Cite
|
Sign up to set email alerts
|

Advances observed in papaya tree propagation

Abstract: Papaya (Carica papaya L.) is a fruit tree of great economic and food interest worldwide. Its propagation can occur both sexually and asexually. Traditionally, it is propagated by seeds; however, vegetative propagation has been often used with the use of in vitro and ex vitro culture techniques. In vegetative propagation, the cutting method has been extensively explored. Research has also been developed using grafting. In recent years, papaya cultivation has also become a model for other fruit plants in the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 75 publications
0
4
0
2
Order By: Relevance
“…These characteristics correspond to the 'Maradol' variety. Furthermore, under the proposed scheme, the selfpollinated flowers of hermaphrodite plants, according to the floral proportion in papaya, expected 66.67% hermaphrodite offspring plants for their next cycle (Santana et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…These characteristics correspond to the 'Maradol' variety. Furthermore, under the proposed scheme, the selfpollinated flowers of hermaphrodite plants, according to the floral proportion in papaya, expected 66.67% hermaphrodite offspring plants for their next cycle (Santana et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Other species such cherimoya (Annona cherimola) have been also maintained in vitro during 250 subcultures (more than 20 years) in our laboratory, maintaining the shoot multiplication rate but loosing most of the rooting capabilities (Encina, unpublished results). To date, we do not found even in the last reviews (Al-Shara et al 2018; Costa et al 2019) any references involving long-term cultures focused to proliferation and preservation of papaya in vitro during long periods of time.…”
Section: Introductionmentioning
confidence: 86%
“…Other species such as cherimoya (Annona cherimola) have been also maintained in vitro for 250 subcultures (more than 20 years) in our laboratory, maintaining the shoot multiplication rate but losing most of their rooting capabilities (Encina, unpublished results). To date, even in the most recent reviews [30,31], we have found no references to long-term cultures focused on the proliferation and preservation of papaya in vitro over long periods of time.…”
Section: Introductionmentioning
confidence: 99%